Pengaruh Konten Giveaway Merchandise Blackpink pada Official Instagram @oreo_indonesia terhadap Citra Merek Oreo - Kurnia, Nabila Indriafly; Astuti, Prida Ariani Ambar (UNIVERSITAS KALBIS, 2025)
Oreo is a brand that collaborates with a Korean girl group, Blackpink. Through the distribution of giveaway merchandise content on the official Instagram @oreo_indonesia. This collaboration through Blackpink merchandise that encourages researchers to find out the effect of Blackpink merchandise giveaway content on the Oreo brand image. This research uses a quantitative approach by conducting a survey of @oreo_indonesia Instagram followers. Using a simple linear regression test, it is known with a positive direction of influence. Which means, if the giveaway content increases, the brand image will also increase. The content indicators that most influence brand image are visual poster indicators that can cause long-term effects or central routes as one of the routes stated in the theory of the Elaboration Likelihood Model.